Positively vivid visions: Making followers feel capable and happy. (October 2019) - Fiset, John; Boies, Kathleen
A number of leadership theories have highlighted the positive impact that a leader's vision can have on follower outcomes. Although significant research has examined the impact of vision, our understanding of the mechanisms underlying this relationship is incomplete. Here, we use self-concept-based theory (Shamir et al., 1993) to explore how the strength of the vision being propounded and the way that it is expressed by leaders influence collective work beliefs. Using a matched sample of teachers and principals, we observe that inspirational visions are positively associated with group affective tone and that future-oriented visions are positively associated with collective efficacy and group affective tone, with all relationships mediated by visioning behaviour. Thus, employees whose leaders exhibit strong visions feel more collectively capable (higher levels of collective efficacy) and happier (higher levels of group affective tone) than employees whose leaders exhibit weak visions, especially when messages are delivered in an emotionally positive way. We conclude that visions contain distinct vision strength themes that differ in terms of their motivating capacity and offer important practical implications and suggestions for future research.